Problems with a Cordless Endodontic Hand Piece when Preparing Severely Curved Root Canals - Maria Giraki; Arno Bauer; Claudia Barthel; Stefan Rüttermann; Susanne Gerhardt-Szep (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
The aim of this study was to describe the shaping ability of a rotary nickel-titanium instrument in combination with different torque-controlled endodontic devices in severely curved root canals of extracted human teeth. Sixty human molars with curvatures ranging from 25° to 69° were embedded in a muffle system and portioned into five horizontal sections (thickness 1.2 mm), starting from the apex. Canals were divided into three groups (n = 20 for each) and were prepared with either a cordless endodontic handpiece (SiroNiti) or two conventional devices (E-MasterTM and Endo IT control) using FlexMaster® instruments and a crown-down preparation technique. We evaluated the frequency of instrument failure, preparation time, loss of working length and differences between pre- and postoperative instrumentation of root canal cross-sections. The root canal area before and after the intervention was determined using area-measuring software. The data were analyzed statistically using a one-way ANOVA followed by a Kruskal-Wallis multiple-comparison Z-test. Significantly higher values for preparation time and instrument failures were observed when using the cordless endodontic handpiece, while using the Endo IT control device resulted in significantly higher values for loss of working length (0.6 mm). Specimens treated with the SiroNiti device showed the greatest significant change from preoperative cross-sections. Preparing root canals using the described devices lead to various problems. The cordless endodontic handpiece produced unsatisfactory results for three of the four parameters analyzed. Thus within the limitations of our study, the SiroNiti device can only partially be recommended for treating curved canals.